Nature-based solutions must be realized - not just proclaimed - in face of climatic extremes - Beierkuhnlein, Carl (ERDKUNDE, 2021)
Natural hazards resulting from climate change are increasing in frequency and intensity. As this is not a linear trend but rather by singularities and anomalies including a broad spectrum of climatic and weather extremes with high temporal and spatial uncertainty, focused avoidance strategies are difficult to prepare. However, the effects of climate change are mostly addressed with outdated ‘business as usual’ approaches by governments and most stakeholders, which are unfit to tackle the complexity of current challenges. Coping action for natural hazards is mostly undertaken during and after such events compensating damage through payments and restoration. In the future, pro-active nature-based solutions are needed for risk mitigation and avoiding severe damage through enhancing all facets of biodiversity from species richness, structural roughness, to spatial heterogeneity of ecosystems. This will not avoid extreme weather events, but it will reduce the damage of increasingly appearing natural hazards. However, this strategy cannot be implemented all of a sudden. Long-term and spatial concepts are needed. For this purpose, currently missing governance structures based on geographical, geoscientific, ecological, meteorological, and societal expertise should be installed. In recent years, a good scientific and knowledge basis for the required solutions has been developed, which now must translate into action. Here, a series of suggestions is compiled for a broad spectrum of extreme events and societal fields, which is far from being complete but should stimulate critically needed creativity and commitment. Nature-based solutions will not deliver a complete protection and cannot be the only kind of action, but we can no longer rely on post-disaster compensation or on the safety illusion of mere engineering and construction works. The efficiency of biodiversity as an insurance for maintaining ecosystem services is well understood. The implementation of nature-based adaptation, coping, and protection measures is less expensive than traditional end-of-the-pipe constructions. It requires an in-depth understanding of interacting processes and trans-disciplinary cooperation based on a broad acceptance in the public. Investments into these solutions would pay off, not tomorrow, but in the future. It is the best sustainable and feasible approach for disaster prevention.